Arterial blood gases` analysis in elite breath-hold divers at extreme depths - Barkovic, I.; Jurilj, Z.; Marinelli, F.; Maricic, V.; Pavlovic, M.; Turk Wensveen, T.; Peršic, V. (European Journal of Applied Physiology, 2023)
Purpose To showcase results of arterial blood gases` analysis in elite breath-hold divers sampled at depths where their total lung capacities are below their residual lung volume on surface.